High-entropy alloy composite coating material and preparation method thereof
By introducing TiC particles into AlCoCrFeNi2.1 high-entropy alloy and heat treatment, a high-entropy alloy composite coating material was prepared, which solved the problem of insufficient wear resistance and hardness of the alloy under harsh environments, and achieved better mechanical properties and high temperature stability.
Patent Information
- Application Number
- CN202411774309.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing AlCoCrFeNi2.1 high-entropy alloy still has room for improvement in wear resistance and hardness under harsh environments such as high temperature and high wear.
High-entropy alloy composite coating material was prepared by introducing TiC particles into the high-entropy alloy matrix and using a heat treatment annealing process. The process includes steps such as high-energy ball milling, laser cladding and heat treatment to ensure uniform distribution of TiC particles and optimize the microstructure of the alloy.
The hardness, wear resistance, high temperature creep resistance and oxidation resistance of the material are significantly improved, so that it maintains excellent performance in extreme working environments.
Smart Images

Figure CN119571313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloy materials, and specifically relates to a high entropy alloy composite coating material and a preparation method thereof. Background Art
[0002] High entropy alloys (HEAs) are a new type of alloy composed of five or more (nearly) equal atomic ratio elements. Due to its special multi-principal element design concept, it has excellent mechanical properties, thermal stability, corrosion resistance and oxidation resistance. 2.1 High entropy alloys have attracted much attention due to their FCC+BCC dual-phase structure, which balances high strength and toughness and exhibits excellent comprehensive properties at high temperatures. However, in the face of harsh working environments, such as high temperature and high wear conditions, the wear resistance and hardness of the alloy still have room for further improvement. Summary of the invention
[0003] In order to solve the deficiencies in the prior art, the object of the present invention is to provide a high entropy alloy composite coating material and a preparation method thereof.
[0004] After heat treatment, the alloy will release internal thermal stress, thereby reducing the internal defects of the alloy. When the physical phase in the alloy changes from a face-centered cubic solid solution phase to a body-centered cubic solid solution phase, the plasticity of the alloy decreases and the hardness increases. Therefore, heat treatment is often used as a post-treatment method to transform the alloy phase structure and optimize the alloy performance. TiC is a hard ceramic particle with high hardness, high melting point and excellent wear resistance. Introducing TiC particles into a high entropy alloy matrix can not only significantly improve the hardness and wear resistance of the alloy, but also improve its high temperature creep resistance and oxidation resistance. The high entropy alloy composite coating material provided by the present invention is obtained by a heat treatment annealing process and by mixing TiC particles with AlCoCrFeNi 2.1 The high entropy alloy composite gives the material better wear resistance and mechanical properties, and can maintain excellent performance in extreme working environments.
[0005] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0006] The present invention provides a method for preparing a high entropy alloy composite coating material, which is characterized by comprising the following steps:
[0007] (1) Weighing each powder according to the following high entropy alloy composite coating material ratio, and performing high-energy ball milling under inert gas protection to obtain a mixed powder;
[0008] In terms of mass percentage, the high entropy alloy composite coating material comprises:
[0009] Al 4.56-5.96wt%
[0010] Co 10.01-13.01wt%
[0011] Cr 8.88-11.48wt%
[0012] Fe 9.53-12.88wt%
[0013] Ni 47.00-57.22wt%
[0014] TiC 0-20wt%
[0015] (2) preparing a high entropy alloy coating by laser cladding process on the mixed powder obtained in step (1);
[0016] (3) heat treating the high entropy alloy coating prepared in step (2) at a temperature of 800-1300° C. for 1.0 h, and quenching the coating with water to room temperature after the heat treatment to obtain the high entropy alloy composite coating material.
[0017] Furthermore, the purity of Al, Co, Cr, Fe, Ni and TiC is ≥99.9%.
[0018] Furthermore, the rotation speed of the high-energy ball mill is 200-500 r / min, the time of high-energy ball milling is 4-8 hours, and the ball-to-material weight ratio is 1:5-1:10, so as to ensure that the powder is fully mixed and the TiC particles are evenly distributed in the metal powder.
[0019] Furthermore, the laser power of the laser cladding process is 1200-2300w, the scanning speed is 400-1000mm / min, the powder feeding speed is 10-20g / min, the laser energy deposition method adopts a single-layer multi-pass path, the spot diameter is 3-5mm, and the overlap rate is 50%.
[0020] Furthermore, the mass percentage of the TiC is 1-20wt%.
[0021] Furthermore, the mass percentage of the TiC is 1-5wt%.
[0022] Furthermore, the temperature of the heat treatment is 800-1200°C.
[0023] Furthermore, the temperature of the heat treatment is 800-1100°C.
[0024] Furthermore, the mass percentage of the TiC is 1-5wt%, and the temperature of the heat treatment is 1100°C.
[0025] Furthermore, in the laser cladding process, the substrate is made of Q235 low-carbon steel, and the oxide layer on the surface of the substrate is removed with an angle grinder, and then polished. Alcohol is used to remove oil stains and impurities, and the substrate is dried. The mixed powder is placed in a laser generator, and high-purity argon is used as a protective gas. The powder is melted using laser energy deposition to ensure the uniformity of the alloy coating.
[0026] The present invention also provides a high entropy alloy composite coating material prepared by the preparation method.
[0027] The beneficial effects of the present invention are:
[0028] The AlCoCrFeNi of the present invention 2.1 +TiC high entropy alloy composite coating materials have the advantages of high hardness, high wear resistance, high corrosion resistance and high temperature stability due to the strengthening effect of heat treatment and TiC particles. After the high entropy alloy coating is prepared by laser cladding process, its microstructure can be changed by heat treatment, and the balance of high strength and ductility of the coating can be achieved through FCC and BCC phase transformation. The addition of TiC particles can refine the coating grain structure and improve the mechanical properties of the coating. The process can be adjusted according to application needs to obtain high entropy alloy composite coatings with different properties, which is convenient for industrial promotion and application. Specifically:
[0029] High hardness: due to the release of residual stress and the change in the amount of FCC phase and BCC phase. Heat treatment makes Ni 2.1 -The microhardness of EHEA is higher than that of the deposited state. Due to the addition of a certain amount of TiC particles, the solid solution strengthening mechanism caused by the Ti element and the second phase strengthening mechanism caused by the TiC particles significantly improve the hardness of the material and extend the service life of the material.
[0030] High wear resistance: When the surface matrix is worn, the TiC particles dispersed in the matrix are exposed, so that the matrix will not be further worn. On the other hand, the strengthening effect of the TiC second phase prevents the matrix from undergoing large deformation, thereby reducing the occurrence of spalling. With the increase of TiC content, the deformation and groove marks of the wear interface are significantly reduced, the interface becomes smoother and smoother, and the debris is greatly reduced, which shows the improvement of wear resistance from the side.
[0031] High corrosion resistance: When the heat treatment temperature increases, the stability of the passive film on the alloy surface decreases, the ion diffusion rate and electrochemical activity increase, and pitting corrosion intensifies. 2.1 EHEA is passivated in NaCl solution, but Cl - The integrity of the passivation film is destroyed, which hinders the self-repair of the passivation and provides conditions for pitting corrosion. 2.1 A corrosion product film is formed instead of a passive film, so pitting is unlikely to occur.
[0032] High temperature stability: Composite materials maintain good structural stability in high temperature environments and are suitable for high temperature applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Example 1Ni 2.1 -SEM micromorphology and EBSD phase distribution diagram of EHEA at different heat treatment temperatures; (a, b) no heat treatment; (c, d) heat treatment at 1100℃; (e, f) heat treatment at 1200℃; (g, h) heat treatment at 1300℃.
[0034] Figure 2 AlCoCrFeNi in different heat treatment states of Example 1 2.1 Hardness and friction and wear properties of deposited layers at room temperature.
[0035] Figure 3 AlCoCrFeNi in different heat treatment states of Example 1 2.1 Hardness and friction and wear properties of deposited layers at room temperature.
[0036] Figure 4 Example 2AlCoCrFeNi 2.1 -TiC x SEM-EDS microstructure of (x=0, 1, 5, 10, 20wt%); (b) T1; (c) T5; (d) T20.
[0037] Figure 5 Example 2AlCoCrFeNi 2.1 -TiC x SEM-EDS microhardness of (x=0, 1, 5, 10, 20wt%); (b) T1; (c) T5; (d) T20.
[0038] Figure 6 EBSD images of the composite coatings with 1-5wt% TiC added and heat treated at 1100℃.
[0039] Figure 7 For Example 8, Example 9 and Comparative Example 3AlCoCrFeNi 2.1 Microhardness of EHEA coating. DETAILED DESCRIPTION
[0040] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In a specific embodiment, the present invention provides a method for preparing a high entropy alloy composite coating material, a heat-treated AlCoCrFeNi 2.1 The high entropy alloy coating preparation process includes the following steps:
[0042] (1) Raw materials preparation:
[0043] a. Select high purity (≥99.9%) Al (5.96wt%), Co (13.01wt%), Cr (11.48wt%), Fe (12.33wt%), Ni (57.22wt%) element powders.
[0044] b. Weigh the powder of each element according to the above ratio.
[0045] (2) Laser cladding process:
[0046] c. The base is made of Q235 low carbon steel. Use an angle grinder to remove the oxide layer on the surface of the base, and then grind it. Use alcohol to remove oil stains and impurities, and dry the base.
[0047] d. Mix the metal element powders prepared in b, and perform high-energy ball milling under the protection of inert gas. The ball milling time is controlled within 4-8 hours to ensure sufficient mixing.
[0048] e. Place the evenly mixed powder in d in a laser generator, use high-purity argon as a protective gas, and use laser energy deposition to melt the powder to ensure the uniformity of the alloy coating.
[0049] f. The laser cladding layer was prepared by laser cladding process. The laser parameters were as follows: laser power 1200w, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single layer multi-pass path, spot diameter 5mm, overlap rate 50%.
[0050] (3) Heat treatment process:
[0051] The high entropy alloy coating prepared in f is subjected to heat treatment as a post-treatment method. The heat treatment process is high temperature annealing and heat preservation for 1.0h followed by water quenching.
[0052] Preferably, the heat treatment method of the high entropy alloy coating is an annealing process, heating the coating to 800°C, keeping it warm for 1.0h and then quenching it with water; specifically, the coating after laser cladding can be cooled to, for example but not limited to, any one of 600°C, 800°C, 1000°C, 1100°C, 1300°C or any range between two thereof. The technical solution is described in detail below through Examples 1-3.
[0053] Example 1
[0054] This embodiment provides a preparation process of a high entropy alloy coating, comprising the following steps:
[0055] (a) Select high purity (≥99.9%) Al (5.96wt%), Co (13.01wt%), Cr (11.48wt%), Fe (12.33wt%), and Ni (57.22wt%) element powders, weigh them, and then high energy ball mill them for 4.0h.
[0056] (b) Laser power 1200w, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single-layer multi-pass path, spot diameter 5mm, overlap rate 50%, to prepare high entropy alloy coating;
[0057] (c) The laser cladding coatings in (b) are heated to 800°C;
[0058] (d) After keeping in the heat treatment furnace for 1 hour, quench with water and cool to room temperature.
[0059] Example 2
[0060] This embodiment provides a preparation process of a high entropy alloy coating, comprising the following steps:
[0061] (a) High purity (≥99.9%) Al (5.96wt%), Co (13.01wt%), Cr (11.48wt%), Fe (12.33wt%), and Ni (57.22wt%) element powders were selected, weighed, and subjected to high energy ball milling for 4.0h.
[0062] (b) Laser power 1200W, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single-layer multi-pass path, spot diameter 5mm, overlap rate 50%, to prepare high entropy alloy coating;
[0063] (c) The laser cladding coating in (b) was heated to 1100°C;
[0064] (d) After being kept in a heat treatment furnace for 1 h, the mixture is quenched in water and cooled to room temperature.
[0065] Example 3
[0066] This embodiment provides a preparation process of a high entropy alloy coating, comprising the following steps:
[0067] (a) High purity (≥99.9%) Al (5.96wt%), Co (13.01wt%), Cr (11.48wt%), Fe (12.33wt%), and Ni (57.22wt%) element powders were selected, weighed, and subjected to high energy ball milling for 4.0h.
[0068] (b) Laser power 1200W, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single-layer multi-pass path, spot diameter 5mm, overlap rate 50%, to prepare high entropy alloy coating;
[0069] (c) The laser cladding coating in (b) was heated to 1300°C;
[0070] (d) After being kept in a heat treatment furnace for 1 h, the mixture is quenched in water and cooled to room temperature.
[0071] In another specific embodiment, the present invention provides a TiC particle reinforced AlCoCrFeNi 2.1 The high entropy alloy composite coating preparation process comprises the following steps:
[0072] (1) Raw materials preparation:
[0073] a. Select high purity (≥99.9%) Al (5.96-4.56wt%), Co (13.01-10.01wt%), Cr (11.48-8.88wt%), Fe (12.88-9.53wt%), Ni (57.20-47.00wt%) metal element powders and TiC (1-20wt%) ceramic particle powders.
[0074] b. Weigh each element powder and TiC powder according to the above ratio.
[0075] (2) Laser cladding process:
[0076] c. The base is made of Q235 low carbon steel. Use an angle grinder to remove the oxide layer on the surface of the base, and then grind it. Use alcohol to remove oil stains and impurities, and dry the base.
[0077] d. The TiC powder prepared in b is mixed with metal element powder and subjected to high-energy ball milling under inert gas protection. The ball milling time is controlled within 4-8 hours to ensure that the TiC particles are evenly distributed in the metal powder.
[0078] e. Place the evenly mixed powder in d in a laser generator, use high-purity argon as a protective gas, and use laser energy deposition to melt the powder to ensure the uniformity of the alloy coating.
[0079] f. The laser cladding layer was prepared by laser cladding process. The laser parameters were laser power 1200w, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single layer multi-pass path, spot diameter 5mm, overlap rate 50%.
[0080] Table 1 Laser process parameters of the embodiment
[0081]
[0082] Preferably, the chemical composition mass fractions of the metal powder are: Al (5.96-4.56wt%), Co (13.01-10.01wt%), Cr (11.48-8.88wt%), Fe (12.88-9.53wt%), Ni (57.20-47.00wt%) and TiC (1-20wt%).
[0083] Preferably, the coating is a high entropy alloy composite coating, for example, but not limited to, any one of TiC (1wt%), TiC (5wt%), TiC (15wt%), and TiC (20wt%) is added. The more TiC particles are added, the more lattice distortion to a certain extent caused by the solid solution of TiC. Lattice distortion increases the resistance to dislocation movement, making slip difficult. This improves the strength and hardness of the coating. The technical solution is described in detail below through Examples 4-7.
[0084] Example 4
[0085] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0086] (a) Selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) and TiC (1wt%) element powders;
[0087] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0088] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0089] Example 5
[0090] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0091] (a) Selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) and TiC (5wt%) element powders;
[0092] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0093] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0094] Example 6
[0095] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0096] (a) Selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) and TiC (10wt%) element powders;
[0097] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0098] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0099] Example 7
[0100] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0101] (a) Selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) and TiC (200wt%) element powders;
[0102] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0103] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0104] In a more preferred specific embodiment, the present invention provides a process for preparing a high entropy alloy composite coating by heat treatment and addition of TiC particles. The technical solution is described in detail below through Examples 8-9.
[0105] Example 8
[0106] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0107] (a) selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) element powders and TiC (1wt%);
[0108] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0109] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0110] (d) The laser cladding coating in (c) was heated to 1100°C;
[0111] (e) After keeping in the heat treatment furnace for 1 h, quench with water and cool to room temperature.
[0112] Example 9
[0113] This embodiment provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0114] (a) selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) element powders and TiC (5wt%);
[0115] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0116] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0117] (d) The laser cladding coating in (c) was heated to 1100°C;
[0118] (e) After keeping in the heat treatment furnace for 1 h, quench with water and cool to room temperature.
[0119] Comparative Example 1
[0120] This comparative example provides a preparation process of a high entropy alloy coating, comprising the following steps:
[0121] (a) High purity (≥99.9%) Al (5.96wt%), Co (13.01wt%), Cr (11.48wt%), Fe (12.33wt%), and Ni (57.22wt%) element powders were selected, weighed, and subjected to high energy ball milling for 4.0h.
[0122] (b) Laser power 1200W, scanning speed 400mm / min, powder feeding speed 10g / min, laser energy deposition method using single-layer multi-pass path, spot diameter 5mm, overlap rate 50%, to prepare high entropy alloy coating;
[0123] Comparative Example 2
[0124] This comparative example provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0125] (a) Selecting high purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), Ni (56.71wt%) and TiC (0wt%) element powders;
[0126] (b) Weigh the element powder and TiC particle powder and then high-energy ball mill for 4.0 h;
[0127] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0128] Comparative Example 3
[0129] This comparative example provides a preparation process of a high entropy alloy composite coating, comprising the following steps:
[0130] (a) High purity (≥99.9%) Al (5.89wt%), Co (12.86wt%), Cr (11.35wt%), Fe (12.19wt%), and Ni (56.71wt%) element powders were selected.
[0131] (b) Weigh the element powder and high-energy ball mill for 4.0 h;
[0132] (c) The laser power was 1200 W, the scanning speed was 400 mm / min, the powder feeding speed was 10 g / min, the laser energy deposition method adopted a single-layer multi-pass path, the spot diameter was 5 mm, and the overlap rate was 50% to prepare the high entropy alloy coating.
[0133] (d) The laser cladding coating in (c) was heated to 1100°C;
[0134] (e) After keeping in the heat treatment furnace for 1 h, quench with water and cool to room temperature.
[0135] In order to distinguish the samples of each embodiment from each other, each sample is named according to the powder characteristics or process sequence. For example, T10 sample represents AlCoCrFeNi with 10 wt% TiC added. 2.1 EHEA coating sample. Sample 3#, representing AlCoCrFeNi with heat treatment temperature of 1000℃ 2.1 EHEA coating sample. C1 represents AlCoCrFeNi with 1wt% TiC added at heat treatment temperature of 1100℃ 2.1 EHEA coating specimen.
[0136] The samples after each embodiment and comparative example were subjected to microhardness and friction and wear tests, and characterized by microhardness measurement and friction and wear tests at room temperature. The Vickers hardness of the coating was measured using a digital microhardness tester with a load of 300g and a dwell time of 15 seconds. The average value of five measurements for each sample was recorded. According to the microhardness test results of each embodiment and comparative example of the present invention, it can be seen that the hardness of the samples (Examples 1-3) at 800℃-1300℃ is compared with that of the unheat-treated sample (Comparative Example 1). Figure 2 As shown, the microhardness values of the samples are 198HV 0.3 、290HV 0.3 、322HV 0.3 、281HV 0.3 and 167HV 0.3 Except for the 1300℃ sample with the lowest hardness, the hardness of the other heat-treated samples is higher than that of the unheat-treated samples. According to ASTM G99-04, the sliding dry wear behavior of the coating was evaluated at room temperature using a ball-on-disk tribometer (MDW-02). Using SiC grinding balls, the test was carried out for 30 minutes at a distance of 5 mm, a speed of 3 m / min, and a load of 20 N. Figure 2 As shown, the friction coefficient of the 800°C heat treatment (2# Example 1) is the lowest. Figure 5 As shown, the hardness of samples T1-T20 (Examples 4-6) is 219.3 HV 0.3 、231.3HV 0.3 、247.7HV 0.3 、253.9HV 0.3 , which are greater than the sample T0 (Comparative Example 2). However, when HTT increases to 1300℃ again, the microstructure coarsening becomes more serious and the difference between the two phases increases. The austenite grains in the microstructure of the sample after heat treatment at 1300℃ are abnormally coarse, which indicates that overheating has occurred, which is the main reason why the hardness of Example 3 is lower than that of Comparative Example 1. Figure 7As shown, AlCoCrFeNi with 5wt% TiC heat treated at 1100℃ 2.1 The hardness of the EHEA coating (C2 Example 9) is the highest compared to the hardness of C0 and C1 (Comparative Example 3 and Example 8), reaching 386.4 HV. 0.3 .
[0137] At the same time, SEM (scanning electron microscope) and EBSD (electron backscatter diffraction) methods were used to analyze the 1#-
[0138] The magnified structural morphology of the four samples was obtained by SEM observation, such as Figure 1 The samples shown all have columnar and dendritic features of the initial FCC and BCC. Table 1 shows the elemental composition of the initial FCC and BCC. Ni & Al are enriched in the BCC phase, Fe & Cr are enriched in the FCC phase, and Co is evenly distributed in each phase. At HTT (heat-treatment temperature) = 800 ° C, short particles began to appear in the FCC phase, which is considered to be the precipitation phase produced by heat treatment. At HTT = 1000 ° C, the short particles in the FCC phase are needle-shaped and short-block-shaped and become coarse. When HTT = 1200 ° C, the needle-shaped precipitation phase disappears, and the short-block precipitation phase is retained. When HTT = 1300 ° C, no precipitation phase is observed. And with the increase of HTT, the initial BCC in the coating becomes more and more coarse.
[0139] Table 2 Deposition AlCoCrFeNi 2.1 Chemical element compositions (wt.%) of initial FCC and BCC phases in EHEA.
[0140]
[0141] Figure 4 The overall SEM morphology of the cross-section of the composite coating with 1-20wt% TiC addition is shown. All elements are uniformly distributed on a macroscopic level, and there is no segregation or ablation of low-melting-point elements. Light gray particles of different morphologies and sizes are distributed between columnar and dendritic structures. The microscopic morphology of the coating was further observed using a scanning electron microscope with a higher magnification. Figure 4 As shown in (a1)(b1)(c1)(d1), EDS surface scanning confirms that the light gray particles are TiC, and the particle size increases with the increase of TiC content. When the TiC content is 1wt%, the TiC particles are polygonal in shape. When the TiC content is 5wt%, the TiC precipitates as approximately round particles. With the further increase of TiC content, the nucleation rate increases significantly. A large amount of TiC tends to grow on smaller TiC particles to form a larger petal-shaped TiC structure.
[0142] Figure 6The EBSD images of the composite coatings with 1-5wt% TiC added and heat treated at 1100°C are shown. Due to the dual effects of adding TiC particles and heat treatment, the grains of the coating microstructure are refined. The texture index in the pole figure (PF) can reflect the bonding strength of the coating to a certain extent. The texture coefficients of the composite coatings (Examples 7-8) that have been heat treated and added with 1-5wt% TiC particles are higher than those of the coatings that have not been heat treated and have not been added with TiC particles (Comparative Example 3). This shows that heat treatment and the addition of TiC particles can enhance the bonding strength of the coating.
[0143] The present invention uses a method of heat treatment and adding TiC particles to prepare AlCoCrFeNi by laser cladding process. 2.1 EHEA coating improves the microhardness and wear resistance of the coating while maintaining the FCC+BCC dual-phase eutectic microstructure. It refines the grains and makes the structure more uniform. The process can be adjusted according to application needs to obtain high-entropy alloy coatings with different properties, which is convenient for industrial promotion and application.
[0144] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high entropy alloy composite coating material, characterized in that: The steps include: (1) Weighing each powder according to the following high entropy alloy composite coating material ratio, and performing high-energy ball milling under inert gas protection to obtain a mixed powder; In terms of mass percentage, the high entropy alloy composite coating material comprises: Al 4.56-5.96wt% Co 10.01-13.01wt% Cr 8.88-11.48wt% Fe 9.53-12.88wt% Ni 47.00-57.22wt% TiC 0-20wt% (2) preparing a high entropy alloy coating by laser cladding process on the mixed powder obtained in step (1); (3) heat treating the high entropy alloy coating prepared in step (2) at a temperature of 800-1300° C. for 1.0-1.2 h, and quenching the coating with water to room temperature after the heat treatment to obtain the high entropy alloy composite coating material.
2. The preparation method according to claim 1, characterized in that: The purity of Al, Co, Cr, Fe, Ni and TiC is ≥99.9%.
3. The preparation method according to claim 1, characterized in that: The rotation speed of the high-energy ball mill is 200-500 r / min, the time of the high-energy ball mill is 4-8 hours, and the weight ratio of the ball to the material is 1:5-1:
10.
4. The preparation method according to claim 1, characterized in that: The laser cladding process has a laser power of 1200-2300w, a scanning speed of 400-1000mm / min, a powder feeding speed of 10-20g / min, a laser energy deposition method using a single-layer multi-pass path, a spot diameter of 3-5mm, and an overlap rate of 50%.
5. The preparation method according to claim 1, characterized in that: The mass percentage of the TiC is 1-20wt%.
6. The preparation method according to claim 1, characterized in that: The mass percentage of the TiC is 1-5wt%.
7. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 800-1200°C.
8. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 800-1100°C.
9. The preparation method according to claim 1, characterized in that: The mass percentage of the TiC is 1-5wt%, and the temperature of the heat treatment is 1100°C.
10. A high entropy alloy composite coating material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-entropy alloy coating material with high wear resistance
CN114574748A
Laser cladding high-entropy alloy coating for mold repair and preparation method of laser cladding high-entropy alloy coating
CN114657554A
Preparation method of high-entropy alloy composite material
CN118166346A
Cited By
High-entropy alloy coating and preparation method thereof
CN120989610A